Pgp3 seroprevalence and associations with active trachoma and ocular Chlamydia trachomatis infection in Malawi: cross-sectional surveys in six evaluation units. - Sarah E Burr; John Hart; Lyson Samikwa; David Chaima; Gretchen Cooley; Diana Martin; Michael Masika; Anthony W Solomon; Robin L Bailey; Khumbo Kalua (PLoS Neglected Tropical Diseases, 2019)
Background Following one to five years of antibiotic mass drug administration (MDA) for the elimination of trachoma as a public health problem, programmes must conduct impact surveys to inform decisions on whether MDA is still needed. These decisions are currently based on the prevalence of trachomatous inflammation-follicular (TF), which, after MDA, correlates poorly with prevalence of ocular Chlamydia trachomatis infection. Methodology/principal findings Impact surveys in six evaluation units (EUs) of Malawi were used as a platform to explore associations between the prevalence of TF, ocular C. trachomatis infection and anti-Pgp3 antibodies one year after the third annual round of MDA. Participants were examined for trachoma using the World Health Organization simplified grading system. Ocular swabs and dried blood spots (DBS) were collected from children aged 1-9 years. Swabs were tested for C. trachomatis DNA using GeneXpert. DBS were assayed for anti-Pgp3 antibodies using ELISA. EU-level prevalence of TF in children aged 1-9 years ranged from 4.7% (95% CI 3.4-6.3) to 7.2% (95% CI 5.8-8.9). Prevalence of C. trachomatis infection in children ranged from 0.1% (95% CI 0.0-0.6) to 0.7% (95% CI 0.3-1.3) while Pgp3 seroprevalence ranged from 6.9% (95% CI 5.4-8.6) to 12.0% (95% CI 10.1-14.0) and increased with age. Conclusions/significance Based on current global policy, the prevalence of TF indicates that a further year of antibiotic MDA is warranted in four of six EUs yet the very low levels of infection cast doubt on the universal applicability of TF-based cut-offs for antibiotic MDA. Pgp3 seroprevalence was similar to that reported following MDA in other settings that have reached the elimination target however the predictive value of any particular level of seropositivity with respect to risk of subsequent infection recrudescence is, as yet, unknown.